PENGARUH CITRA PARIWISATA OLAHRAGA TERHADAP NIAT MELAKUKAN KUNJUNGAN ULANG YANG DIMEDIASI OLEH PENGALAMAN WISATAWAN - Ugi Nugraha; Roli Mardian; Ely Yuliawan (Jurnal Sporta Saintika, 2021)
This study aimed to analyze the effect of the sport tourism image on the revisit intention mediated by the tourists experience. The populations of this research were tourists who visited ​the Danau Sipin Tourism Area, Jambi City. The sample in this study was selected by accidental sampling method. This method was chosen because it is difficult to determine the visitor data for tourist attractions because it changes every day, so the samples were the tourists that the researcher met randomly in the ​​Danau Sipin Tourism Area, Jambi City. Data analysis was per.formed using the Partial Least Square (PLS) approach with the help by the Smart-PLS 3.0 software. The results showed that the sports tourism image had a significant effect on the revisit intention. The results of this study also indicated that the sports tourism image indirectly affected revisit intention mediated by the tourists experience. Keywords: Revisit intention, sport tourism image, tourists experience